Comparison of the Aerodynamic Characteristics of the NACA0012 Airfoil at Low-to-Moderate Reynolds Numbers for any Aspect Ratio - García-González, Antonio Luis; Martínez-Aranda, Sergio; Velázquez-Navarro, José; Parras-Anguita, Luis; Del-Pino-Peñas, Carlos Manuel (Scientific & Academic Publishing, 2016)
This experimental work deais with the influence of the angle of attack (AoA) and the chord based Reynolds number (Rec) on the lift and drag coefficients for a low-aspect-ratio NACA0012 airfoil. In addition, we provide novel general correlations for the mínimum drag coefficient together with the ratio between the máximum lift and the mínimum drag coefficient for different Reynolds numbers and several aspect ratios. after comparing our experimental data with other research works. This Information is very useful for future validation of nmnerical simulations. Furthennore. we observe that the change in the aerodynamic characteristics are linked to the variations in the linear slope of the lift coefficient as function of AoA for any aspect ratio. thus finding a critical Reynolds number Rec = 105 at which the slope satúrales its valué and the máximum of the polar curve changes its upward trend.
Keywords: Aviones - Alas; Aerodinámica; Low Reynolds Number; Wing Aerodynamics; Aspect ratio; Wingtip Vortex